PERCEPATAN PENUNTASAN WAJIB BELAJAR 9 TAHUN DI KABUPATEN KEPAHIANG - Zikrullah Zikrullah; Rohiat Rohiat; Aliman Aliman (Manajer Pendididikan, 2017)
The purpose of this study was to describe the acceleration program compulsory 9 years in the Department of Education Youth and Sports District Kepahiang. This research uses descriptive study with a qualitative approach. Data collection techniques taking interviews, observation and documentation. Subjects were Head of Youth and Sports Kepahiang District, head of basic education, Head of Basic Education Curriculum, Staff Planning Education Association, Member of Parliament Kepahiang District Education Commission, Office of the Chief District ministry of religion Kepahiang. While the data analysis was done with descriptive analysis, inductive and deductive. Research results show that the vision and mission the Department of Education Youth and Sports District Kepahiang Kepahing has implemented two programs form. Coordination between the Department of Education Youth and Sports District Kepahiang and dynamically interwoven Kepahiang ministry of religion Office in accordance with the duties of each agency.Achievement of the program have a breakthrough both categories.